Inhibitory effects of 2-substituted-1-naphthol derivatives on cyclooxygenase I and II - Boonsong Kongkathip (2018)
Naphthol derivatives, 2-(3′-hydroxypropyl)-naphthalen-1-ol (2), 2-(3′-hydroxy-2′-methylpropyl)-naphthalen-1-ol (3) and 2-(3′-hydroxy-2′,2′-dimethylpropyl)-naphthalen-1-ol (7) were synthesized and already reported by our group. Therefore in this paper we described further synthesis of their ether derivatives, 3-(1-methoxy-naphthalen- 2-yl)-propan-1-ol (4), 3-(1-methoxy-naphthalen-2-yl)-2methyl-propan-1-ol (5), 3-(1-methoxy-naphthalen-2-yl)-2,2-dimethyl-propan-1-ol (8), 2-(3-methoxy-propyl) -naphthalen-1-ol (10) and 2-(3-methoxy-2,2-dimethyl-propyl)-naphthalen-1-ol (13). Compounds 4, 5 and 8 were prepared by methylation of compounds 2, 3 and 7, respectively while compounds 10 and 13 were prepared in good yield from naphthols 2 and 7, respectively. When tested for inhibitory activity, five compounds (2, 3, 7, 10 and 13) showed preferential inhibition of COX-2 over COX-1, while compounds 4, 5 and 8 lacked inhibitory effect on either the COX-1 or COX-2 isozyme. The structure-activity relationships of these naphthols analyzed by docking experiments, indicated that the presence of hydroxyl group at C-1 position on the naphthalene nucleus enhanced the anti-inflammatory activity towards COX-2 via hydrogen bonding to the COX-2 Val 523 side chain. When this hydroxyl group was replaced by methoxy group, there was no inhibition. C-2′ Dimethyl substituents on the propyl chain also increased the inhibitory activity. All active compounds have the C-1 hydroxyl group aligned so as to form hydrogen bond with Val 523. The results provide a model for the binding of the naphthol derivatives to COX-2 and facilitate the design of more potent or selective analogs prior to synthesis. © 2005 Elsevier Ltd. All rights reserved.